2022
DOI: 10.1002/ppul.25850
|View full text |Cite
|
Sign up to set email alerts
|

Food insecurity and mental health during the COVID‐19 pandemic in cystic fibrosis households

Abstract: Background: The COVID-19 pandemic impacted many households due to shelter-in-place orders and economic hardship. People with cystic fibrosis (CF) experienced increased food insecurity compared to the general population before the pandemic, even though adequate food access is needed to maintain nutrition goals associated with improved health-related outcomes. Little is known about the impact the pandemic had on the food insecurity of people with CF and their families.Objective: To investigate how the COVID-19 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Stress levels, a potential contributor to poor mental health, have been found to increase as food insecurity deteriorates (Rahman et al, 2021). Other studies have found that the number of households experiencing food insecurity has increased during the COVID-19 pandemic (Lim et al, 2022). Moreover, food-insecure subjects were more likely to have an abnormal mental health screen compared to food-secure subjects (Lim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Stress levels, a potential contributor to poor mental health, have been found to increase as food insecurity deteriorates (Rahman et al, 2021). Other studies have found that the number of households experiencing food insecurity has increased during the COVID-19 pandemic (Lim et al, 2022). Moreover, food-insecure subjects were more likely to have an abnormal mental health screen compared to food-secure subjects (Lim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Another important factor that most participants felt contributed significantly to their FI was the COVID-19 pandemic, which has led to unprecedented levels of FI due to increased food prices, disrupted community support networks, increased rates of unemployment and school/daycare closures [24,25]. The pandemic has also led to increased reports of worse mental health and self-care in food-insecure persons with CF [26]. The CFF recently conducted a national survey to assess trends in FI screening and interventions prior to and during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…2 Both food insecurity and mental health are areas of emphasis in the cystic fibrosis (CF) community, 3,4 and previous research suggests that people with CF experienced higher rates of food insecurity and worsening mental health during the COVID-19 pandemic. 5 This is particularly concerning because food insecurity among people with CF was linked to worse health outcomes before the COVID-19 pandemic, suggesting that the pandemic likely exacerbated already existing challenges. 3,6 We describe a clinical program, developed and deployed at the onset of the COVID-19 pandemic, to identify and support families at-risk for food insecurity and mental health concerns related to the pandemic.…”
Section: To the Editormentioning
confidence: 99%